Neuron-specific enolase, histopathological types, and age as risk factors for bone metastases in lung cancer - Yang Zhou; Wen-Zhao Chen; Ai-Fen Peng; Wei-Lai Tong; Jia-Ming Liu; Zhi-Li Liu (Tumor Biology, 2017)
Lung cancer is a malignant tumor with high metastatic ability and bone is the most common site of distant metastasis of it. However, the independent risk factors for bone metastases of lung cancer remain largely to be elucidated. Here, we conducted a retrospective study to evaluate the correlation between clinical–pathological parameters, serum levels of neuron-specific enolase and CYFRA21-1, and bone metastases in lung cancer patients. The results revealed that patients with bone metastases were younger than those without metastases. Adenocarcinoma was the most frequent type of histopathology in patients with bone metastases. And the incidence of bone metastasis in patients with adenocarcinoma was significantly higher than those with other histopathological subtypes ( p  < 0.001). Furthermore, the serum concentration of neuron-specific enolase was significantly higher in patients with bone lesions than those without bone metastases. Multivariate logistic regression analysis showed that patients’ age (odds ratio = 1.024, p  < 0.001), concentrations of neuron-specific enolase (odds ratio = 1.212, p  = 0.004), and histopathological types (odds ratio = 0.995, p  = 0.001) were the independent risk factors for bone metastases in patients with lung cancer. Thus, physicians should pay attention to these factors in order to identify bone metastasis earlier while patient was primarily diagnosed as having lung cancer.